1989
DOI: 10.1016/0014-5793(89)80669-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor modulation of glucose‐induced electrical activity in mouse pancreatic B‐cells

Abstract: Acetyicholine (1-10/zM) depolarized the membrane and stimulated glucose-induced bursts of electrical activity in mouse pancreatic B-cells. The acetylcholine effects were mimicked by muscarine while nicotine had no effect on membrane potential. Pirenzepine, an antagonist of the classical M l-type muscarinic receptors, but not gallamine (1-100 gM), an antagonist of the classical M2-type receptors, antagonized the acetylcholine action on glucose-induced electrical activity (ICs0 =0.25/zM). Bethanechol, an agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…These oscillations had a reduced duration and amplitude and were accompanied by a marked potentiation of pulsatile 5-HT/ insulin release. The overall cholinergic response resembles that observed in terms of electrical activity recorded from whole mouse islets, where acetylcholine evoked a membrane depolarization with an initial phase of continuous spiking followed by bursts of electrical activity with a lower duration and higher frequency (Hermans et al, 1987;Santos and Rojas, 1989). The initial response is likely to reflect Ca 2+ release from internal stores via the PLC/ 1,4,5-IP 3 system (Gilon and Henquin, 2001;Hermans and Henquin, 1989).…”
Section: Discussionsupporting
confidence: 56%
“…These oscillations had a reduced duration and amplitude and were accompanied by a marked potentiation of pulsatile 5-HT/ insulin release. The overall cholinergic response resembles that observed in terms of electrical activity recorded from whole mouse islets, where acetylcholine evoked a membrane depolarization with an initial phase of continuous spiking followed by bursts of electrical activity with a lower duration and higher frequency (Hermans et al, 1987;Santos and Rojas, 1989). The initial response is likely to reflect Ca 2+ release from internal stores via the PLC/ 1,4,5-IP 3 system (Gilon and Henquin, 2001;Hermans and Henquin, 1989).…”
Section: Discussionsupporting
confidence: 56%
“…Increased Parasympathetic Activity in Pancreatic ␤ Cells-In several species, including the mouse, insulin secretion is stimulated by the parasympathetic system via cholinergic muscarinic receptors (27,28). To investigate whether the parasympathetic nervous system plays a role in the postabsorptive hyperinsulinemia of the ␣ 1b -AR Ϫ/Ϫ mice, the insulin plasma levels were measured 30 min after the injection of atropine or methyl-atropine in 6-h fasted mice.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, thapsigargin, an ER Ca2+ pump blocker which depletes the ER of Ca2+, also produces high-frequency 'muscarinic bursting' in mouse B-cells (Bertram et al 1995). Cholinergic-induced depletion of Ca2+ from ER may be the mechanism underlying the increase in the frequency of glucoseinduced membrane potential oscillations (bursts) in response to Oxo-m or other cholinergic agonists (Cook et al 1981; Santos & Rojas, 1989). Depolarization in the absence of glucose most probably reflects the activation of a voltage-independent current since the membrane potential is too negative to result in the activation of traditional Na+ and Ca2+ currents (Naumov et al 1994;Satin et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, sustained ACh-potentiated insulin release depends on extracellular Ca2+, indicating that Ca2+ influx is also involved (Garcia, Hermans & Henquin, 1988; Boschero et al 1995). It has been suggested that cholinergic agonists depolarize the B-cell membrane (Cook, Crill & Porte, 1981) by inhibiting K+ currents (Santos & Rojas, 1989) or by increasing the influx of Ca2+ (Sanchez-Andres, Ripoll & Soria, 1988;Hughes, Chalk & Ashcroft, 1990) and/or Na+ (Gilon & Henquin, 1993;Hiriart & Ramirez-Mendeles, 1993). In addition, we have proposed that muscarinic agonists depolarize B-cell by activation of the non-selective, voltage-independent current, ICRAC .…”
Section: Introductionmentioning
confidence: 99%